O poema é um animal: obscuros bestiários de Herberto Helder - Carolina Anglada de Rezende (2014)
Using the poetic experience of portuguese writer Herberto Helder, this study analyzes certain representations of animals in his work in order to relativise the traditionally construed theoretic places proposed by other fields of knowledge, such as Philosophy, Anthropology, and Literary Theory. At first, the helderian 'lyrical machine' and its operations ofreversibility and metamorphosis are presented, as well as considerations partaining to particular aspects of this poet's work. We investigate, along these lines, the ontological rule of humans with the intent to create methodological pathways for the reflection regarding animal otherness, which stands as the center of the present research. As the poet recovers a decadent genre such as the bestiary for his intents and purposes, Helder avails himself of animality in an operation of criticism which, in the writing of becoming, proposes new approaches and perceptions of the unknowable. Finally, we establish relationships between the appropriation of tradition and the gesture of translation, which, in Helder, are processes that affirm writing as an opening to the foreign as well as to otherness